2013
DOI: 10.1111/joor.12116
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lingual and hypoglossal nerve function and quality of life in head and neck cancer

Abstract: Sensorimotor impairment of the tongue has the potential to affect speech and swallowing. The purpose of this study was to critically examine the effects of nerve preservation and reinnervation after reconstruction of the base of tongue on patient-perceived outcomes of quality of life (QoL) related to speech and swallowing through completion of the EORTC QLQ-H&N35 standardised questionnaire. Thirty participants with a diagnosis of base of tongue cancer underwent primary resection and reconstruction with a radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…Patients with normal upper aerodigestive tract anatomy and biomechanics may be able to masticate and swallow with their entire upper aerodigestive tract anesthetized, patients who have undergone surgery for head and neck cancer may rely on sensation in order to compensate for altered anatomy and biomechanics. A study by Elfring et al found that patients with repaired/intact hypoglossal and/or lingual nerves had significantly better social contact, social eating, swallowing, and dry mouth scores after oropharyngeal resection and reconstruction, however, it is not discussed in detail here because it did not include a comparison between sensate and insensate.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Patients with normal upper aerodigestive tract anatomy and biomechanics may be able to masticate and swallow with their entire upper aerodigestive tract anesthetized, patients who have undergone surgery for head and neck cancer may rely on sensation in order to compensate for altered anatomy and biomechanics. A study by Elfring et al found that patients with repaired/intact hypoglossal and/or lingual nerves had significantly better social contact, social eating, swallowing, and dry mouth scores after oropharyngeal resection and reconstruction, however, it is not discussed in detail here because it did not include a comparison between sensate and insensate.…”
Section: Methodsmentioning
confidence: 98%
“…Studies using subjective measures rely on data, such as patient satisfaction and quality of life surveys administered at various points throughout the postoperative course, as well as subjective measurements of speech intelligibility . For other measures, a listener most commonly subjectively rated speech outcomes utilizing scales, such as unintelligible speech to normal intelligible speech .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Impairment of tongue function can severely affect quality of life. 1 Therefore, it is paramount to restore the tongue's main function after oncologic (hemi)glossectomy. Because of its complex anatomy, it is challenging to restore bulk, mobility, and sensibility in order for the reconstructed tongue to be functional.…”
Section: Introductionmentioning
confidence: 99%